Periprocedural Myocardial Infraction: A Review Article - Irma Kamelia Pratiwi; Fandy Hazzy Alfatta; Teguh Aryanugraha; Muhamad Bayu Aji; Putri Annisa Kamila; Ratna Pancasari; Ayu Asri Devi; Krishna Ari Nugraha; Mohammad Saifur Rohman (Heart Science Journal, 2022)
Percutaneous coronary intervention can be associated with several complications such as periprocedural myocardial infarction (PPMI) that was deﬁned as an elevation of CK-MB >3 times the upper limit of the normal range in at least two blood samples with a normal range of baseline value, prolonged ischemia as demonstrated by persistent chest pain (>20 min), or new pathological Q waves seen on the electrocardiogram.By epidemiology, periprocedural myocardial infarction was happen in about 6 – 7% patient underwent PCI and associated with adverse outcome. Therefore it is important to identify the possible factors to detect, prevent and manage this event.